2014
DOI: 10.1002/clen.201300866
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Bioavailability of Heavy Metals in Sediments of Riverine Wetlands Located in the Huaihe River Watershed, China

Abstract: Fractionations and mobility of heavy metals in sediment cores taken from the Suoxu River located in the Huaihe River watershed, China, were carried out and assessed. The results revealed that the total concentrations of Cd, Cr, Cu, Pb, and Zn reached up to 0.38, 70.2, 92.1, 35.9, and 227.0 mg kg−1 in sediment cores from the upstream, 0.19, 66.5, 27.4, 29.1, and 80.1 mg kg−1 from the midstream and 0.18, 49.4, 24.2, 28.5, and 64.8 mg kg−1 from downstream of the river, respectively. The concentrations of heavy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This lowest APD value of MB‐B, together with its highest value of Span (2.464 ± 0.448) indicated a lack of homogeneity in size for the smallest microbeads tested, which would make them more likely to be ingested by filter‐feeding bivalves and small planktonic organisms, accumulating at higher levels of the food chain. Besides this fact, a smaller particle size could offer a higher adsorption capacity for different pollutants . In addition, MB‐B was the cheapest of the four brands tested, which makes it a particularly attractive option for consumers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lowest APD value of MB‐B, together with its highest value of Span (2.464 ± 0.448) indicated a lack of homogeneity in size for the smallest microbeads tested, which would make them more likely to be ingested by filter‐feeding bivalves and small planktonic organisms, accumulating at higher levels of the food chain. Besides this fact, a smaller particle size could offer a higher adsorption capacity for different pollutants . In addition, MB‐B was the cheapest of the four brands tested, which makes it a particularly attractive option for consumers.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that particle size is an important factor affecting the concentration of their associated pollutants [23]. The results of this study revealed that the highest concentration of heavy metals was measured in microbeads with the lowest APD; that is, MB-B and MB-A, accounting for 93.9% of total heavy metals in bi-distilled water and 74.4% of total heavy metals in TUE, where the interference of residual organic matter could act as a sorption competitor for microbeads.…”
Section: Heavy Metal Sorption Capacitymentioning
confidence: 99%
“…It is well established that soil organic matter is positively correlated with available heavy metal contents and represents an important heavy metal sink (Ferraz et al, 2000;Bartoli et al, 2012;Yuan et al, 2015). Soil organic matter, a complex and heterogeneous component initially ascribing to the physical, chemical and biological evolution of biopolymeric materials, is further decomposed to fulvic and humic acids, kerogen and black carbonaceous materials via various degrees of diagenetic processes (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“… Note: The data required in the table are all derived from previous research [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. “—” represents that relevant data could not be found in the literature.…”
Section: Figurementioning
confidence: 99%